ANALISA FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY (STUDI KASUS PADA PERUSAHAAN SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BEI PERIODE 2009-2014) - Diajeng Tri Anggarawati; Fuad Fuad (Diponegoro Journal of Accounting, 2016)
Audit Delay is past the deadline BAPEPAM, would result in a delay in the publication of the financial statements. The purpose of this study was to analyze the effect of moderating the reputation of auditors to the effect of institutional ownership, profitability, company size, and the solvency of the audit committee to audit delay food and beverages sector companies listed on the Stock Exchange 2009-2014 period. The study population was the whole financial data of companies listed on the Stock Exchange 2009-2014 period. The sampling method used in this research is purposive sampling method. The sample used in this study is the food and beverages sector companies listed on the Stock Exchange in a row in 2009-2014. The data used are secondary data from BEI. The analysis technique used is moderated regression analysis. Based on this research, institutional ownership, and firm size negatively affect audit delay. Profitability, solvency audit committee and has no effect on audit delay. Based on the results of MRA (Multiple Regression Analysis), the auditor's reputation can be inferred moderate the effect of variable institutional ownership, the size of the company and the solvency of the audit delay, but the reputation of the auditor does not moderate the influence of variables of profitability, and the audit committee to audit delay.